Pengembangan Media E-Comic Bermuatan Kearifan Lokal Batak Toba pada Pembelajaran Membaca Teks Narasi Kelas III UPT. SDN 12 Sei Suka Deras - Tio Minar Tindaon; Halimatussakdiah; Winara; Edizal Hatmi; Albert Pauli Sirait (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop an e-comic media integrated with Batak Toba local wisdom for teaching narrative text reading to Grade III students at UPT SDN 12 Sei Suka Deras and to determine the feasibility, practicality, and effectiveness of the developed media. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The participants of this study were 25 students of Grade III A at UPT SDN 12 Sei Suka Deras. Data were collected through observation, interviews, questionnaires, documentation, and narrative reading performance tests. The instruments included material expert validation sheets, media expert validation sheets, assessment rubric validation sheets, teacher response questionnaires, student response questionnaires, and narrative reading assessment rubrics. The developed media, named PETRA TOBA (Petualangan Literasi Batak Toba), was created using the Pixton Edu platform and integrated the Batak Toba local wisdom value of Dalihan Na Tolu. The results showed that the e-comic media was highly feasible, with material expert validation reaching 97%, media expert validation 96%, and assessment rubric validation 94%. The practicality of the media was categorized as very high based on teacher responses of 90% and student responses of 81.37%, resulting in an average practicality score of 87.12%. The effectiveness of the media was demonstrated by the improvement in students’ average scores from 55.28 in the pre-test to 86.41 in the post-test, with an N-Gain score of 0.713 (71.3%), categorized as effective. Therefore, the developed e-comic media is considered feasible, practical, and effective for narrative text reading instruction in elementary school.